The Global Cosmopolitan Mindset Lessons from the New Global Leaders - Brimm, Linda (Palgrave Macmillan UK, 2018)
A growing number of people in the world have embraced globalization and actively seek opportunities to live, study, and work in other cultures. Highly talented and deeply motivated, they have been shaped by the new political/economic opportunities, technological realities and personal choices that have configured their lives. They are the Global Cosmopolitans. Professor Linda Brimm, whose last book, Global Cosmopolitans: The Creative Edge of Difference, defined and named this phenomenon, now introduces the Global Mindset and Skillset and examines what are the dilemmas and opportunities of composing a global life over time. Dr. Brimm has interviewed Global Cosmopolitans at different life stages and has garnered insights from those on the front line of the global economy. She describes how they understand the life dilemmas and opportunities implicit in navigating the rapidly changing global environment and how they learn from the lives they are creating. While these are people using the expertise developed over their global journey to manage change, lead organizations, make a difference in the world, or create their own ventures, she helps us understand what they have learned and how this global learning opportunity has contributed to the development of a Global Cosmopolitan Mindset and Skillset. This book relates some of the stories that global leaders and entrepreneurs have shared with Dr. Brimm. These concrete examples help us understand what the individuals have learned from their personal experience. Emerging from these stories are the unique attitudes and skills that are necessary to confront life challenges, embrace change and take steps to create new life chapters. Whether you are a Millennial considering joining this 'Cosmopolitan Club', an existing Global Cosmopolitan reflecting on what is next, someone in mid-career contemplating an international move, part of an organization trying to develop its responses to a global workforce, or a leader considering who can best run global organizations, this book provides a unique insight into the Global Cosmopolitan Mindset and Skillset - as well as the challenges and rewards of pursuing a global life.